Representasi Isu Kesehatan Mental Dalam Video Musik Heavy Oleh Grup Musik Linkin Park - Comawati, Ni Luh Ary; Alit Suryawati, I Gusti Agung; Sugiarica Joni, I Dewa Ayu (E-Jurnal Medium; Vol 2 No 1 (2021): Jurnal Ilmu Komunikasi Vol 2 No 1 Tahun 2021, 2021)
As one of the mass communication media, music video comes as a medium for communicating message to the audience through audio and visual. Linkin Park's music video “Heavy” is one of the music video that depicts about one's struggle against inner demons. The study aims to look at representations of mental health issues in Linkin Park's “Heavy” music video. Researcher used qualitative approaches and examined data with concepts of mental health issues, Hall’s representation theory and the Triangle Meaning theory from Peirce. The results showed that “Heavy” music video represents mental health issues with behaviors that show symptoms of mental state including: (1) anxiety symptoms shown through repetitive behaviour and body language (2) symptoms of anger emotions are shown as throwing things and fighting (3) emotional symptoms of sadness indicated by body language, (4) difficulty completing daily work and alcohol consumption. Keywords : Mental health issue, Music Video, Charles Peirce